Labor Productivity in Peru: 1997-2007 - Tello, Mario D. (Pontificia Universidad Católica del Perú. CENTRUM, 2012)
The purpose of this paper was to decompose the changes in labor productivity of the Peruvian economy into the between- and within-sector effects using 39 sectors in terms of production structure for the period 1997-2007. This sectoral level of analysis was contrasted with a similar, although extended, decomposition at firm level using a sample of 7096 formal manufacturing enterprises for the period 2002-2007. At the sectoral level, the evidence shows that the between-sector or reallocation effects dominate most of the changes in labor productivity in the economy. However, at the firm level, the within-sector effects dominate the changes in labor productivity for the sample of formal firms. The role played by the informal sector in the determination of Peruvian labor productivity may explain the differences. On one hand, the informal sector tends to reduce the within-sector effects because of its significant employment share in manufacturing and its low level of labor productivity. On the other hand, the informal sector tends to increase the between-sector effects, given its buffer feature of generating employment in both crisis and boom periods.
Keywords: Between- and within-sector effects; Job creation; Job destruction; Labor productivity; https://purl.org/pe-repo/ocde/ford#5.02.04